Large bowel obstruction caused by a colonic polyp - Ishimaru, Naoki; Fujikawa, Hirohisa; Kobayashi, Yoshifumi (Journal of Surgical Case Reports, 2022)
Abstract A large bowel obstruction (LBO) is an emergency condition that requires early diagnosis and prompt treatment, and it is also crucial to identify the cause of the obstruction. Here, we describe a 76-year-old woman who presented to the hospital with a 1-day history of abdominal pain and vomiting and was diagnosed with LBO. Endoscopic findings showed that the cause of the LBO was initially determined to be a Bormann Type I tumour in the sigmoid colon. However, the surgery was performed later; the pathological findings led to the diagnosis of colonic obstruction caused by a colonic polyp in the sigmoid colon narrowed by chronic diverticulitis. Colonic polyps rarely cause LBO. Poor observation due to colonic stenosis can mask the morphology of the lesion. In cases of LBO, colonic polyps should be differentially diagnosed in addition to colon cancer.